A Mobile Application as Didactic Material to Improve Learning on Distributed Architectures - Ortiz, Guadalupe; Garcia-de-Prado, Alfonso; Boubeta-Puig, Juan; Cwierz, Halina (2020 International Conference on Computational Science and Computational Intelligence (CSCI), 2020)
The university has been applying a teaching methodology based on continuous assessment over the last few years. The main advantage of this methodology is that students acquire the knowledge gradually, so that they consolidate it better in their memory; however, they run the risk of forgetting what was studied in the first parts of the course when they finish it. To motivate students to review what they learnt, we have implemented an augmented reality mobile application and methodology with which students review the contents of the subject through the serious game. Moreover, the game focuses on the specific difficulties of each student by reinforcing those questions that are most difficult for them. In this paper, we also present how the game has been customized for various courses from the Degree in Computer Science and Engineering at the University of Cadiz and which results were obtained.